2022
DOI: 10.1101/2022.10.10.511654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the Human ATAD2 AAA+ Histone Chaperone Reveals Mechanism of Regulation and Inter-subunit Communication

Abstract: ATAD2 is a non-canonical ATP-dependent histone chaperone and a major cancer. Despite widespread efforts to design drugs targeting the ATAD2 bromodomain, little is known about the overall structural organization and AAA+ domains of ATAD2. Here, we present the 3.1 Å cryo-EM structure of human ATAD2 in the ATP state, showing a shallow hexameric spiral that binds a peptide substrate at the central pore. The spiral conformation is locked by an N-terminal linker domain (LD) that wedges between the seam subunits, thu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…We showed that Abo1 directly interacts with the N-terminal domain (NTD) of Spt16 using the FIN helix located at the N-terminal region (NTR). The NTR of Abo1 exhibits low sequence conservation among its homologues, suggesting that functional differences between Abo1 homologues may be linked to this N-terminal variability (27,29,30). The precise role of the NTR in Abo1’s function remains unclear, but it may serve as a domain for protein-protein interaction domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that Abo1 directly interacts with the N-terminal domain (NTD) of Spt16 using the FIN helix located at the N-terminal region (NTR). The NTR of Abo1 exhibits low sequence conservation among its homologues, suggesting that functional differences between Abo1 homologues may be linked to this N-terminal variability (27,29,30). The precise role of the NTR in Abo1’s function remains unclear, but it may serve as a domain for protein-protein interaction domain.…”
Section: Discussionmentioning
confidence: 99%
“…Abo1 has been identified as one of FACT's interaction partners (20)(21)(22)(23)(24)(25)(26). Abo1 is one of the histone chaperones that bind histone H3-H4 and regulates the chromatin dynamics (20,27).…”
Section: Introductionmentioning
confidence: 99%